A vivência do refúgio de mulheres migrantes: uma análise da afetividade nos contextos de São Paulo e Paris - Zozzoli, Cécile Diniz (2015)
In the light of the Socio-Historical Psychology and its articulation with the Espinosa philosophy, the various sociological studies about social ties and ruptures and about gender, migration and refuge, this work is intended to investigate the processuality of the senses, affections and relations of the life in the refuge of migrant women in their process of social exclusion/inclusion. It is assumed that the affectivity centered analysis brings elements to elucidate at which point the different analyzed situations are oriented towards the development or the decrease of the power of action, probably, in an alternate movement between these two poles. Therefore, it is sought to know the history of the refuge process; to investigate the senses that women have of themselves and the senses present in the relations with the place of origin, with the hosting place and their public services, as well as with other people in diverse situations of everyday life; to analyze how such migration affects the family relations and which role the family plays in this process; to understand the configurations of prejudice and discrimination that, possibly, are directed to refugee women; to analyze the perspectives that these women has of the future and their life projects; to study how the gender issues relate to the senses and affections evolved in the refuge process. To meet these objectives, the research follows the field observation methodological principles, that was carried by semi-structured interviews in the cities of São Paulo and Paris. The selected group of subjects is formed by 20 women that migrated in search for refuge, from which 9 were located in Brazil and 11 in France. With the purpose of organizing the analysis material, there are established 4 main categories concerning relational affiliations of the migrants: family, job, citizenship and elective relationships. Overall, the reflections enable to observe an accumulation of transformations and ruptures of the relations and social ties belonging to the women's living that affected them on contradictory and opposite thoughts and feelings in the process of exclusion from their country of origin and perverse inclusion on the foreign countries. In this sense, the fluctuation of the power of action and the affections that characterized the living of the refugees indicates a frame of political ethical suffering, but also of resistance and of desire for freedom